Upgrade of a quasioptical code PARADE for fusion DEMO: introducing relativistic electron dynamics. (1st August 2022) - Yanagihara, K.
Abstract: Here we report on the upgrade of the quasioptical code PAraxial RAy DEscription (2019 Phys. Plasmas 26 072112) to introduce the relativistic effect for electron cyclotron resonance heating and current drive on fusion DEMO reactors, e.g. JA-DEMO, where the electron temperature is sufficiently high (almost 35 keV). By fully considering the relativistic effect, it is found that the outside launch used in many tokamaks is not suitable for localized heating in JA-DEMOdue to the contamination of spatially widespread absorption at relativistically down-shifted higher-harmonic resonance. It is proposed to adopt a top launch to avoid this issue, and is shown that top launch can improve the localization of the heating without degrading the current drive efficiency.